The Revitalization of Patung Sigale-Gale Batak Toba Folklore into Teaching Material in English Subject for Junior High School - Martha Gracella SGR Ritonga; Bambang Nur Alamsyah Lubis; Widia R Simamora; Rifa Situmorang (English Teaching and Linguistics Journal (ETLiJ), 2021)
This study deals with information of Batak Toba folklore Patung Sigale-Gale into learning materials at Junior High School. The objective of this study is to develop complete story of Patung Sigale-Gale Batak Toba folklore into teaching materials in English Subject for Junior High School. This study used descriptive qualitative approach in analyzing the data. The data of this research are interview and observation in Samosir Island, North Sumatera, source of data were an informant who knew about the history of Patung Sigale-Gale. The result of this study, there were able to write complete story about Patung Sigale-Gale that can be used as teaching materials in the classroom, especially in English Subject.